2020
DOI: 10.3390/sports8120153
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Traditional and Stabilization-Oriented Exercises on Deep Stabilization System Function in Elite Futsal Players

Abstract: Background: This study aimed to compare the effect of traditional and stability-oriented strength exercises on trunk stability and deep stabilization system (DSS) activation in elite futsal players. Methods: Twenty elite futsal players (21–34 years, 180 ± 13 cm, 79 ± 15 kg) were randomly divided into a group that performed stability-oriented exercises and a group that performed traditional strength exercises. Both interventions lasted for 10 weeks and included 25 strength training sessions. Main outcome measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…The core training method showed a small positive effect, though it does not include strengthening a primary mover for handball throwing. In early training phases in youth categories, players can benefit from core training, but its efficiency is primarily for muscle stabilization ( Jebavy et al, 2020 ) and lasts for a few weeks(Jebavý, 2012). Core training’s intensity can be increased by progressive exercise selection and programming with progressive overloads in exercise intensity, including external loads.…”
Section: Discussionmentioning
confidence: 99%
“…The core training method showed a small positive effect, though it does not include strengthening a primary mover for handball throwing. In early training phases in youth categories, players can benefit from core training, but its efficiency is primarily for muscle stabilization ( Jebavy et al, 2020 ) and lasts for a few weeks(Jebavý, 2012). Core training’s intensity can be increased by progressive exercise selection and programming with progressive overloads in exercise intensity, including external loads.…”
Section: Discussionmentioning
confidence: 99%
“…Per paskutinius kelis metus mokslinių tyrimų (Park et al, 2021;Hyun, Young, Jochua, 2022;Raghuveer et al, 2022), nagrinėjančių dinaminės neuroraumeninės stabilizacijos metodikos efektyvumą, padaugėjo. Dauguma tyrimų (Davidek, Andel & Kobesova, 2018;Jebavy et al, 2020;Park et al, 2021) nagrinėja šios metodikos poveikį sportuojančių asmenų jėgai, stabilumui ir motoriniams įgūdžiams. Nors metodikos efektyvumas įrodytas ir įvairioms neurologinėms bei griaučių raumenų ligoms (Sharma & Yadav, 2020), tačiau vis dar reikia daugiau tyrimų, siekiant ištirti šios metodikos efektyvumą pacientams po galvos smegenų infarkto.…”
Section: įVadasunclassified
“…DNS offers a rehabilitative and manual approach that practitioners can use to improve functional treatment and optimize the movement system in athletes by rebuilding stability performance [7][8][9][10][11][12][13][14] . One of the latest research on applying DNS in a sample of elite futsal players and race walkers indicates that DNS therapy effectively increases performance and balance 15,16 . Research has shown that the level of tension in the abdominal wall is signi cantly higher during DNS exercises than in other forms of exercise.…”
Section: Introductionmentioning
confidence: 99%